1991
DOI: 10.1073/pnas.88.3.824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long and short forms of the prolactin receptor on prolactin-induced milk protein gene transcription.

Abstract: The biological activities of long and short forms of the prolactin receptor have been compared. These two receptors expressed in mammalian cells were shown to bind prolactin with equal high affinity. The ability of these different forms to transduce the hormonal message was estimated by their capacity to stimulate transcription by using the promoter of a milk protein gene fused to the chlormphenicol acetyltransferase (CAT) coding sequence. Experiments were performed in serum-free conditions to avoid the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
114
0
2

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(123 citation statements)
references
References 30 publications
7
114
0
2
Order By: Relevance
“…CHO K1 cells were grown and transfected as previously described [14] with modifications [11]. Transfection of plasmid DNA was performed using the calcium phosphate procedure, with 40 gg DNA in each precipitate.…”
Section: Cell Culture and Transient Expression Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…CHO K1 cells were grown and transfected as previously described [14] with modifications [11]. Transfection of plasmid DNA was performed using the calcium phosphate procedure, with 40 gg DNA in each precipitate.…”
Section: Cell Culture and Transient Expression Proceduresmentioning
confidence: 99%
“…Each precipitate was obtained with 6 gg of the CAT plasmid to be tested, 12 gg of the pCHll0 plasmid coding for 13-galactosidase (Pharmacia), 12 gg of the plasmid pER2-3 carrying the rabbit mammary prolactin receptor cDNA [15], and 10 gg of carrier DNA (genomic sonicated DNA from salmon testes). After ~5-h incubation in the presence of the precipitate, the cells were washed and cultured in serum-free medium [14] containing hormones. Two dishes were incubated with cortisol (60 nM).…”
Section: Cell Culture and Transient Expression Proceduresmentioning
confidence: 99%
“…In humans, two PRLr isoforms have been identified: the long (Boutin et al 1989) and a novel intermediate isoform, recently identified in our laboratory (Clevenger et al 1995a). All PRLr isoforms are homologous in their extracellular and transmembrane domain; alternative mRNA splicing accounts for the differing sizes of the cytoplasmic domain, with the exception of the Nb2 mutant form, which is believed to result from a mutation in the exon encoding for rat PRLr intracellular domain (Ali et al 1991). The extracellular domain of the PRLr demonstrates homology via a tryptophan-serine box motif with the gene superfamily of cytokine receptors that includes the receptors for IL-2 to IL-7, GM-CSF, GH, and erythropoietin (Bazan 1989).…”
Section: Mediation Of Prl Function By Prlr Structurementioning
confidence: 99%
“…Three isoforms of PRLr have been cloned in the rat (see Fig. 2): the 'short' (PRLr-S, approximately 291 amino acids, approximately 45 kDa), 'long' (PRLr-L, approximately 592-598 amino acids, 80-85 kDa), and intermediate (PRLr-I, a deletion mutant missing amino acids 323-520 of the PRLr-L isoform, found in the PRL-dependent rat T-cell lymphoma line Nb2; 393 amino acids, approximately 65 kDa) (Boutin et al 1988, Ali et al 1991. In humans, two PRLr isoforms have been identified: the long (Boutin et al 1989) and a novel intermediate isoform, recently identified in our laboratory (Clevenger et al 1995a).…”
Section: Mediation Of Prl Function By Prlr Structurementioning
confidence: 99%
“…In addition to these PRLR isoforms found in vivo, an intermediate form, lacking 198 aa in the cytoplasmic domain with respect to the long form, has been identified in the rat pre-T lymphoma Nb2 cell line (20). Studies of the in vitro biological properties of PRLR isoforms have shown that the long and intermediate, but not the short form, are able to transactivate milk protein gene promoters (21,22). However, involvement of both long and short PRLR isoforms in cell proliferation has also been proposed (23).…”
mentioning
confidence: 99%